Supply Fee for In-house Fiber Networks — A Critical Review of a New Tool for Accelerating the Roll-out of Gigabit Connections - Torsten J. Gerpott (Wirtschaftsdienst)
Abstract From 1 December 2021, a supply fee for in-house fiber networks is temporarily introduced into the Telecommunications Act. This article reviews the provisions of the new Paragraph 72 of this Act. Economic policy recommendations are derived to develop regulations that are a fairer balance of interests between tenants, real estate companies/lessors and operators of fixed public telecommunication networks as well as a stronger acceleration of the roll-out of fiber-to-the-building connections.